(3GdbGehS GdeMjW hGdbCHhS GdhSjWs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3BNQgG (B:s
(3ef HGH GdVGO , aUd GdgGA , bhdg (B: (3gjV GdWGFQ SdMg , hbO gGV jgjV aUd GdjGA jVV GdLQh aJM Yjfjg dZI ai GdVGO Je GdLRA GdChd ef GdbGehS s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdeaQOGJ hGdYHGQGJ HGdMeQI ade JXgQ ai GdJUhjQs
(3fSNI QGHYIs
(3jJab ChdgG eY Chd fSNI (B" (3eJMa TjQfhGFi (B- (3WTbfO s
1043 " (3HGNJdGa ai HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs